2014
DOI: 10.1021/es404474x
|View full text |Cite
|
Sign up to set email alerts
|

Natural Gas Pipeline Leaks Across Washington, DC

Abstract: Pipeline safety in the United States has increased in recent decades, but incidents involving natural gas pipelines still cause an average of 17 fatalities and $133 M in property damage annually. Natural gas leaks are also the largest anthropogenic source of the greenhouse gas methane (CH4) in the U.S. To reduce pipeline leakage and increase consumer safety, we deployed a Picarro G2301 Cavity Ring-Down Spectrometer in a car, mapping 5893 natural gas leaks (2.5 to 88.6 ppm CH4) across 1500 road miles of Washing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
173
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(177 citation statements)
references
References 29 publications
2
173
2
Order By: Relevance
“…Recent measurement campaigns in different cities in the USA and Europe also revealed that significant leaks occur in specific locations (e.g. storage facilities, city gates, well and pipeline pressurization/depressurization points) along the distribution networks to the end-users (Jackson et al, 2014a;McKain et al, 2015). However, methane emissions can vary a lot from one city to another depending in part on the age of city infrastructure (i.e.…”
Section: Oil and Natural Gas Systemsmentioning
confidence: 99%
“…Recent measurement campaigns in different cities in the USA and Europe also revealed that significant leaks occur in specific locations (e.g. storage facilities, city gates, well and pipeline pressurization/depressurization points) along the distribution networks to the end-users (Jackson et al, 2014a;McKain et al, 2015). However, methane emissions can vary a lot from one city to another depending in part on the age of city infrastructure (i.e.…”
Section: Oil and Natural Gas Systemsmentioning
confidence: 99%
“…Gilman et al (2013) analyzed extensive VOC measurements at the same site in Colorado during the winter of 2011, confirming an abundance of alkanes associated with the oil and NG production operations in northeastern Colorado based on differences in chemical signatures (e.g., i-pentane/n-pentane ratios and relative amounts of acetylene to propane) between urban sources and oil/gas well emissions. There have also been studies to estimate the emissions of pollutants in the eastern US from NG production, processing, transmission and distribution (Jackson et al, 2014;Roy et al, 2014).…”
Section: R Ahmadov Et Al: Understanding High Wintertime Ozone Pollumentioning
confidence: 99%
“…We identified 25 "leaks" exceeding 2.5 ppm methane over 21 miles of road in all study areas. Thus, the combined density (number of leaks per mile) for all 3 routes was approximately one leak per mile, much lower than findings in Boston and Washington [7,8] but comparable to other cities driven in EDF's partnership project, such as several areas in Dallas, TX, which showed one leak for every two miles driven. The leak with the highest concentration of methane in our study areas was recorded at 10.7 ppm ( Table 1).…”
Section: Weather Conditionsmentioning
confidence: 53%
“…All routes together covered a total of approximately 21 miles of urban roads. Following previous work [7,9], a "leak" was defined as a methane reading of higher than 2.5 ppm. The analyzer was pre-set to take measurements at a frequency of one hertz and general observations were made and recorded during and after the route, including the methane baseline readings of ambient air, and weather observations.…”
Section: Investigated Routesmentioning
confidence: 99%
See 1 more Smart Citation